A Non-enzymatic glucose sensor via uniform copper nanosphere fabricated by two-step method. (December 2021) - Yu, Miaomiao; Weng, Zhankun; Hu, Jing; Zhu, Xiaona; Song, Hangze; Wang, Shenzhi; Cao, Siyuan; Song, Zhengxun; Xu, Hongmei; Li, Jinhua; Wang, Zuobin
Highlights: Homogeneous Cu nanospheres were obtained by pulsed-laser ablation of Cu2 O ethanol dispersion. The size of Cu nanospheres can be finely tuned by changing the irradiation time. Cu nanospheres had an excellent selectivity and sensitivity for glucose. Abstract: Herein, we explored an effective way to obtain uniform copper nanoparticles by irradiating Cu2 O microparticles in ethanol with a 1064 nm laser. The morphology, structure and chemical composition of as-prepared copper nanoparticles were characterized by scanning electron microscopy, transmission electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction and X-ray photoelectron spectroscopy. It is interesting that the diameter of obtained spherical copper nanoparticles can be finely tuned by changing the irradiation time. Moreover, we also found that the particle size of copper nanoparticles can be reduced to ~63 nm when the irradiation time is 30 min. Inspired by the fast-developing non-enzymatic glucose sensors, the electrochemical activity of the copper nanoparticles toward glucose in alkaline media was further investigated. Notably, the electrochemical results reveal that the prepared copper nanoparticles possess a good prospect in non-enzymatic glucose sensor.